Late Diagnosis of Biliary Atresia in an Infant- A Call for Early Cholestasis Screening and Timely Referral - Yovani Savitri; Rendi Aji Prihaningtyas; Bagus Setyoboedi; Sjamsul Arief (MEDICINUS, 2026)
Background: Biliary atresia (BA) is a progressive, fibroinflammatory cholangiopathy and the leading cause of pediatric liver transplantation. Early diagnosis and timely Kasai portoenterostomy (KPE), ideally within the first 45–60 days of life, are critical to preserving native liver function and delaying disease progression. However, in many settings, delayed recognition and referral remain major barriers. Case: A 3-month-and-22-day-old female infant presented with persistent jaundice, acholic stools, and hepatosplenomegaly. Despite the onset of symptoms as early as day 3 of life, referral to a tertiary center was significantly delayed. Laboratory tests showed elevated liver enzymes (aspartate aminotransferase/AST 142 U/l, alanine aminotransferase/ALT 109 U/l, gamma-glutamyl transferase/GGT 1554 U/l, alkaline phosphatase/ALP 572 U/l), total bilirubin 9.84 mg/d, and direct bilirubin 8.31 mg/dl. Two-phase abdominal ultrasonography showed findings consistent with BA, including absence of the gallbladder and a positive triangular cord sign. Liver biopsy showed advanced-stage fibrosis (F3–F4), confirming the diagnosis of BA. Conclusions: Due to the delayed diagnosis and the presence of advanced liver damage, the golden period for effective KPE was missed, making liver transplantation the only definitive treatment option. This case highlights the urgent need for improved screening and early referral systems toenhance outcomes in infants with BA.